2019
DOI: 10.1093/jxb/erz323
|View full text |Cite
|
Sign up to set email alerts
|

Differential activity of F-box genes and E3 ligases distinguishes sexual versus apomictic germline specification in Boechera

Abstract: A comprehensive tissue type-specific transcriptional study identifies 45 genes consistently differentially expressed during Boechera sexual as compared with apomictic germline specification, suggesting their relevance for apomixis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(44 citation statements)
references
References 100 publications
(188 reference statements)
1
42
0
Order By: Relevance
“…Consistently, comparative transcriptome analysis in sexual and apomictic Boechera [103], Bohemeria tricuspis [97], and Hypericum perforatum [62] suggest that differential activity of genes involved in cell-cycle regulation, hormonal pathways, signal transduction, ubiquitinylation and protein degradation, and epigenetic regulatory pathway are involved in determining and sustaining megasporogenesis in either reproductive mode (Figure 3). To narrow down the number of candidate genes and to disentangle part of the effects of ploidy and species differences, differential expression analysis was recently applied to compare four apomictic versus two sexual Boechera accessions [103]. Thereby LAM and RNA-Seq have been combined to analyze gene expression in reproductive nucellus tissues harboring the AIC or MMC [103].…”
Section: Transcriptional Analysis Identifies Genes Differentially Regmentioning
confidence: 55%
See 2 more Smart Citations
“…Consistently, comparative transcriptome analysis in sexual and apomictic Boechera [103], Bohemeria tricuspis [97], and Hypericum perforatum [62] suggest that differential activity of genes involved in cell-cycle regulation, hormonal pathways, signal transduction, ubiquitinylation and protein degradation, and epigenetic regulatory pathway are involved in determining and sustaining megasporogenesis in either reproductive mode (Figure 3). To narrow down the number of candidate genes and to disentangle part of the effects of ploidy and species differences, differential expression analysis was recently applied to compare four apomictic versus two sexual Boechera accessions [103]. Thereby LAM and RNA-Seq have been combined to analyze gene expression in reproductive nucellus tissues harboring the AIC or MMC [103].…”
Section: Transcriptional Analysis Identifies Genes Differentially Regmentioning
confidence: 55%
“…This discrepancy might potentially be explained by master regulators which control complex programs of gene activity. Transcriptional analyses to identify genes differentially expressed in sexual as compared to apomictic plants have been presented for a variety of species including Pennisetum ciliare and Pennisetum glaucum [83,84], Panicum maximum [85,86], Poa pratensis [87,88], Brachiaria brizantha [89,90], Paspalum notatum and Paspalum simplex [91][92][93][94], Eragostris curvula [95], Medicago falcata [96], Boehmeria tricuspis [97], Hypericum perforatum [62,98], Hieracium [99,100], Boechera [101][102][103], and also for Citrus [76] ( Table 2). These studies provide evidence for temporal deregulation of the gene regulatory processes governing sexual reproduction in apomicts and identify large numbers of up to hundreds of genes to be differentially expressed.…”
Section: Transcriptional Analysis Identifies Genes Differentially Regmentioning
confidence: 99%
See 1 more Smart Citation
“…Enzyme Class (EC) distribution comparison of the two sets of DEGs showed that all the enzyme classes had more sequences in single samples than in fused samples except for the EC class Ligases (Fig 5). Various ligase enzymes were identified in fused samples including E3 ubiquitin-protein ligase previously shown to play a role in sexual development [47]. GO category representations in single samples were mostly dominated with metabolic activities (carbohydrate, lipid and protein), oxidation-reduction process, vesicle transport, cytoskeleton and cellular and intracellular movements (S7-S9 Figs).…”
Section: Resultsmentioning
confidence: 99%
“…These results can be interpreted as fused cells primarily engaged in ATP-mediated, DNA-related processes, likely reflecting their sexual nature. Among these, E3 ubiquitin ligase [47] and PHD-Finger [74] have been implicated to play a role in sexual development of plants. E3 ubiquitin ligase has a similar functional domain (i.e., RING-finger to Zip3), a meiosis specific gene and a member of the ZMM group known to play roles in crossover and SC assembly [54, 75].…”
Section: Discussionmentioning
confidence: 99%